Analysis of Student Interests in the Department of Physics Education: University of Muhammadiyah Makassar - Riskawati Riskawati; Andi Arie Andriani; Yusri Handayani; Nurfazlina Nurfazlina (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2021)
In the last three years based on SBMPTN data, interest in the Physics Education Department has decreased drastically in various Public universities in Indonesia which has an impact on private universities, especially at Unismuh Makassar. The desired research objective is to analyze the factors that influence the interest of prospective students towards the Department of Physics Education at Unismuh Makassar. Quantitative descriptive research is the type of research used with the population of senior high school in Gowa Regency which consists of a sample of 50 class XII students from Public senior high school 1 Gowa, Public senior high school 19 Gowa, senior high school Handayani Sungguminasa, andsenior high school Aksara Bajeng. Questionnaire is an instrument used to obtain research data which was analyzed by exploratory factor analysis (EFA). The results of the analysis in this study obtained 4 factors that influence the interest of prospective students towards the Department of Physics Education at Unismuh Makassar, namely personal and parental motivation factors, environmental factors that like Physics Education, physics content factors, and employment factors.